Introducing an agricultural app to vegetable farmers: A pilot study in Lam Dong, Vietnam - Bui, Trang; Pham, T.H.; Kawarazuka, Nozomi; Schreinemachers, Pepijn; Liu, Yanyan (International Potato Center, 2022)
Plantix is an agricultural app developed by a private company based in Germany which offers a diagnosis and advice for more than 30 crops. It has great potential as a new form of extension service complementing a traditional face-to-face extension service. The CGIAR Plant Health Initiative seeks to introduce the app as part of a package of innovations available for integrated pest and disease management to facilitate behavioral change among farmers. Plantix has been widely used in India but has not yet become very common in Vietnam. The aim of this pilot study was to test the usability of Plantix app for progressive rural vegetable growers in Don Duong District, Lam Dong Province, Vietnam. A group of 8 farmers (1 woman and 7 men) participated in the training on use of the app and provided feedback after a two-week trial. The results show that the farmers are very interested in using Plantix. Some of the male participants were already familiar with the symptoms of regular pests and diseases. The app can be very useful for them when they start growing new crops, when there are new pests and diseases, and when they have difficulties distinguishing one disease from others with similar symptoms. Some of the farmers suggested the need for additional information concerning the prediction of pests and diseases at a very early stage before spread in the community. They also suggested the need for information about new generation pesticides.